SCIENCE TEACHERS’ BEHAVIOURAL INTENTION TO USE METAVERSE-BASED LEARNING PLATFORMS: A CONCEPTUAL PAPER - Wider, Clarice; Lay , Yoon Fah; Shaafi, Nur Farha (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The emergence of metaverse-based learning platforms has introduced new possibilities for immersive, interactive, and collaborative science education. These environments are particularly relevant to science teaching because they can support the visualisation of abstract or invisible scientific phenomena, virtual experimentation, inquiry-based learning, and STEM interaction. However, existing research on educational metaverse adoption has focused mainly on student users and general technology acceptance models, with limited attention to science teachers as pedagogical decision-makers who determine whether such platforms are instructionally useful and practically manageable. This concept paper proposes a framework to explain science teachers’ behavioural intention to use metaverse-based learning platforms. Using a conceptual synthesis approach, the paper integrates literature on technology readiness, technology self-efficacy, and technology acceptance. The framework incorporates optimism and innovativeness as positive dimensions of the Technology Readiness Index, together with technology self-efficacy, perceived usefulness, and perceived ease of use. By integrating the Technology Readiness Index, Social Cognitive Theory, and the Technology Acceptance Model, the framework explains how teachers’ readiness and confidence may shape their perceptions of usefulness and ease of use, which subsequently influence behavioural intention. Rather than merely applying TAM to a new technological context, this paper extends TAM by theorising the antecedent roles of teachers’ technology readiness and self-efficacy in shaping acceptance beliefs toward immersive science learning environments. The framework also offers practical implications for teacher preparation, platform design, and policy planning related to metaverse-supported science education.